First-phase ejection fraction predicts response to cardiac resynchronization therapy and adverse outcomes. (25th November 2020) - Gu, H; Baldeep, S; Fang, L; Webb, J; Jackson, T; Claridge, S; Razavi, R; Chowienczyk, P; Rinaldi, C
Abstract: Background: Cardiac Resynchronization Therapy (CRT) is an important therapeutic treatment for chronic heart failure. However, even in carefully selected cases up to 40% of patient fail to respond. First-phase ejection fraction (EF1), the ejection fraction up to the time of maximal ventricular contraction, is a novel and more sensitive echocardiographic measure of early systolic function. Purpose: We examined the value of EF1, to predict response to CRT and clinical outcomes after CRT. Methods: We analysed echocardiograms from 197 patients who underwent CRT between 2009 and 2018 and were followed to determine clinical outcomes. Results: Volumetric response rate (reduction in end-systolic volume ≥15%) was 92.3% vs. 12.1%, for those with EF1 in the highest vs. lowest tertiles (p<0.001). A cut-off value of 11.9% for EF1 had >85% sensitivity and specificity for prediction of response to CRT; on multivariate logistic regression analysis incorporating previously defined predictors, EF1 was the strongest predictor of response (OR: 1.563, 95% CI: 1.371–1.782, p<0.001) (table 1). EF1 was also the strongest predictor of a clinical composite score (OR: 1.115, 95% CI: 1.044–1.191, p=0.001). Improvement in EF1 at 6 months after CRT implantation (6.5±5.8% vs 1.8±4.3% in responders vs. non-responders, p<0.001) was the best predictor of heart failure re-hospitalization and death after median follow-up of 29.2 months (HR: 0.819, 95% CI:0.765–0.876, p<0.001). Conclusion: EF1 is a promising marker to identify patients likely to respond to CRT and most likely provides a measure of myocardial viability that determines response. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation, Wellcome/EPSRC Centre for Medical Engineering